Harper's illustrated biochemistry - Rodwell, Victor W.; Bender, David A.; Botham, Kathleen M.; Kennelly, Peter J.; Weil, P. Anthony (Lange medical book., 2015)
Presents integrated coverage of biochemical disease and clinical information to provide a clear, succinct review of the fundamentals of biochemistry that every student must understand in order to succeed in medical school